Credit Market Competition and Liquidity Crises - Carletti, Elena; Leonello, Agnese (Review of Finance, 2019)
Abstract We develop a model where banks invest in reserves and loans, and trade loans on the interbank market to deal with liquidity shocks. Two types of equilibria emerge, depending on the degree of credit market competition and the level of aggregate liquidity risk. In one equilibrium, all banks keep enough reserves and remain solvent. In the other, some banks default with positive probability. The latter equilibrium exists when competition is weak and large liquidity shocks are unlikely. The model delivers several implications concerning the relationship between competition, aggregate credit, and welfare.